THE DISCOURSE OF (RE)MOTHERHOOD IN ONLINE MEDIA: A Critical Study of the Corruption News on Tempo.co - Dedees, Adek Risma; Noviani, Ratna (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2020)
The news report of Tempo.co about both Ahmad Fathanah and Ratu Atut Chosiyah corruption cases took the discourse of mother and women as the main idea. Mother and women were involved in both cases that tend to be reported exaggeratedly with a huge sensation by using connotation dictions. Media disclosed not only their scandal in corruption but also personal and private life. The motherhood feature of those women become the underlined a major issue in the news. This research focused on three concerns: the discourse formation of (re)motherhood in the news report of both corruption cases, the subject position of mother and women in the news, and the reason why the discourse of mother and women become the main topic in the news report. Critical discourse analysis by Sara Mills was used for showing how media has constructed subject-object and reader positioning on the news. The result showed that the discourse of motherhood was not only reproduced by the nation, but also by the news in online media (Tempo.co). Media has ideological instruments (i.e. wording, grammar, and reader position) to narrate, to evaluate, and more important to define the role of mother and women to fix with the conventional socio-cultural values. They have represented mother and women as independent and modern subject and at the same time, they also circumscribed the definition to make sure that they remain in the ideal type: as the guardian of the family, the companion of the husband, and the guide of the children. To cite this article (7th APA style): Dedees, A. R. & Noviani, R. (2020). The Discourse of (re)motherhood in Online Media: A Critical Study of the Corruption News on Tempo.co. Journal Communication Spectrum, 10(1), 24-37. http://dx.doi.org/ 10.36782/jcs.v10i1.2003